Penatalaksanaan Holistik Pasien Remaja Akhir Usia 19 Tahun Dengan Tuberkulosis Rontgen Positif (Kategori I) Melalui Pendekatan Kedokteran Keluarga - Sabrina Fazriesa; Azelia Nusadewiarti (CV. Jasa Sukses Abadi, 2020)
According to WHO in the Global TB Report 2017, Indonesia ranks third out of six countries which account for 60% of TB cases worldwide, after China and India. Prevention and control of TB risk factors is done in a way that is to cultivate clean and healthy living behavior, to cultivate cough ethical behavior, to maintain and improve the quality of housing and the environment in accordance with healthy home standards, increase endurance, handling of TB comorbidities, the application of prevention and control TB infection in Health Care Facilities, and outside Health Care Facilities. Patient Mr. P, 19 years old, has been diagnosed with primary pulmonary tuberculosis (ICD 10 A16.0). Having concerns about lack of adherence to taking medication. Limited knowledge of patients and their families about the disease and the right lifestyle according to the illness. Interventions were conducted regarding education and motivation to take medications regularly, always control according to schedule, cough ethics, ways to prevent TB transmission and side effects that might arise during treatment. After an evaluation, the patient and family's knowledge about the disease and the importance of taking medication regularly is quite good. Mr. P started to have daily routine activities, exercising regularly and taking medicine regularly with his mother as PMO. Family doctor services in pharmacological and non-pharmacological therapy are able to solve health problems and improve the quality of life of patients.